Pengaruh Knowledge Management Terhadap Kinerja Pegawai Pada Dinas Lingkungan Hidup Kabupaten Luwu - Ade nurul aenun; Finarsih amruddin; Nurmalasari asis; Andi nasrullah; Erwina (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to determine the effect of Knowledge Management on employee performance at the Luwu Regency Environmental Service office. The type of research used is associative research with a quantitative approach. The population and sample of this research were 23 employees in the office studied. Data was obtained using a questionnaire in the form of a Likert scale. From the results of simple regression estimates, it can be seen that knowledge management has a significant effect on employee performance at the Luwu Regency Environmental Service Office (DLH).